Effects of plant growth regulators toward callus regeneration of cavendish banana - Zainal Abidin, Nur Suraya Anis (2018)
Male flowers of banana have potential to be used as explants for tissue culture of Cavendish banana which is in a sub-group of AAA. The aim of this study was to investigate the effects of concentration of different plant growth regulators toward callus induction and to identify the best part of male flowers for callus initiation. The male flowers of Cavendish banana were cultured on MS medium supplemented with 2,4-D (0.1 mg/ml, 0.5 mg/ml, 0.25 mg/ml, and 0.125 mg/ml), NAA (0.1 mg/ml, 0.5 mg/ml, 0.25 mg/ml, and 0.125 mg/ml), 2,4-D + NAA (0.5 mg/ml + 0.5 mg/ml, 0.5 mg/ml + 0.25 mg/ml, and 0.5 mg/ml + 0.125 mg/ml) and MS medium itself by using part 1 of male flowers. Part 2 of male flowers were cultured with MS medium supplemented with BAP (1.0 mg/ml, 2.0 mg/ml, 4.0 mg/ml, 8.0 mg/ml, 12.0 mg/ml), 2,4-D (1.0 mg/ml, 2.0 mg/ml, 4.0 mg/ml, 8.0 mg/ml, 12.0 mg/ml), 2,4-D + IAA (2.0 mg/ml + 0.1 mg/ml, 2.0 mg/ml + 0.5 mg/ml), 2,4-D + NAA (2.0 mg/ml + 0.1 mg/ml, 2.0 mg/ml + 0.5 mg/ml) and 2,4-D + IAA + NAA ( 2.0 mg/ml + 0.1 mg/ml + 0.1 mg/ml, 2.0 mg/ml + 0.5 mg/ml + 0.5 mg/ml). Explants that consist of BAP turned into green color. While other responsive explants formed globar shape of creamy and the morphology of explants were changed. BAP concentrations of 2.0 mg/ml, 4.0 mg/ml and 12.0 mg/ml showed the most responsive explants. While for 2,4-D plant growth regulator with concentration of 1.0 mg/ml and 2.0 mg/ml resulted to be the most optimum concentrations for callus induction. The present study was established for making some analysis depending on the parts of male flowers and also by using difference plant growth regulators with difference concentrations.